S5.4 Identifying knowledge gaps in the evidence base for repeat screening of women with chlamydia and gonorrhoea: challenges to public health action. (10th July 2011) - Bernstein, K
Abstract : There is strong evidence that repeat chlamydia and gonorrhoea infections among women are associated with adverse reproductive health outcomes. However, effective interventions to reduce re-infection are not well-articulated or well-coordinated in STD control programs. Gaps in knowledge about the immunology of chlamydial and gonococcal infections coupled with a poor understanding of adolescent and young adult sexual networks limit progress towards developing effective interventions. This presentation will review the current epidemiology of repeat chlamydia and gonorrhoea among women and highlight the operational challenges to implementing programmatic responses to reducing the burden and impact of repeat infection, including increasing rescreening rates, use of partner delivered therapy, and other approaches to interrupt ongoing transmission in high prevalence sexual networks.